2021
DOI: 10.48550/arxiv.2102.11633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The first GeV flare of the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447

Andrea Gokus,
Vaidehi S. Paliya,
Sarah M. Wagner
et al.

Abstract: Context. On 2019 October 25, the Fermi-Large Area Telescope observed the first ever γ-ray flare from the radio-loud narrow-line Seyfert 1 galaxy PKS 2004−447 (z = 0.24). Prior to this discovery, only four sources of this type had shown a flare at Gigaelectronvolt energies. Aims. We report on follow-up observations in the radio, optical-UV, and X-ray bands that were performed by ATCA, the Neil Gehrels Swift observatory, XMM-Newton, and NuSTAR, respectively, and analyse these multi-wavelength data with a one-zon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…inated by a power-law component coming from the relativistic jet, while the thermal Comptonization model coming from the disk corona accounts for only 2% of the total flux (Gallo et al 2006;Kreikenbohm et al 2016;Berton et al 2019a). It is worth mentioning that Gokus et al (2021) did not detect any component associated with the accretion disk in their analysis of PKS 2004-447 X-ray spectrum observed after the flare, and this is in good agreement with our conclusions. If the jet flux is strongly enhanced, while the corona contribution does not change significantly, the latter will likely become too weak to be detected.…”
Section: Lines and Continuumsupporting
confidence: 91%
See 4 more Smart Citations
“…inated by a power-law component coming from the relativistic jet, while the thermal Comptonization model coming from the disk corona accounts for only 2% of the total flux (Gallo et al 2006;Kreikenbohm et al 2016;Berton et al 2019a). It is worth mentioning that Gokus et al (2021) did not detect any component associated with the accretion disk in their analysis of PKS 2004-447 X-ray spectrum observed after the flare, and this is in good agreement with our conclusions. If the jet flux is strongly enhanced, while the corona contribution does not change significantly, the latter will likely become too weak to be detected.…”
Section: Lines and Continuumsupporting
confidence: 91%
“…This result is in agreement with what was found by (Gallo et al 2006), who derived A(V) = 1.9 ± 1.5 from the AAT spectrum 3 . As they already pointed out, this extinction is significantly higher than what can be estimated from the X-ray spectra, which instead show negligible absorption, as confirmed by more recent observations (Kreikenbohm et al 2016;Berton et al 2019a;Gokus et al 2021). They also suggested that a possible explanation for this is a very different gas/dust ratio than what is seen in the Milky Way, and the jet may play a role in this by transferring material from the nucleus into the NLR.…”
Section: Hα Regionsupporting
confidence: 53%
See 3 more Smart Citations